The hero of this book : a novel - McCracken, Elizabeth (Ecco, an imprint of HarperCollinsPublishers, 2022)
"Ten months after her mother's death, the narrator of The Hero of This Book takes a trip to London. The city was a favorite of her mother's, and as the narrator wanders the streets, she finds herself reflecting on her mother's life and their relationship. Thoughts of the past meld with questions of the future: Back in New England, the family home is now up for sale, its considerable contents already winnowed. The narrator, a writer, recalls all that made her complicated mother extraordinary--her brilliant wit, her generosity, her unbelievable obstinacy, her sheer will in seizing life despite physical difficulties--and finds herself wondering how her mother had endured. Even though she wants to respect her mother's nearly pathological sense of privacy, the woman must come to terms with whether making a chronicle of this remarkable life constitutes an act of love or betrayal. The Hero of This Book is a searing examination of grief and renewal, and of a deeply felt relationship between a child and her parents. What begins as a question of filial devotion ultimately becomes a lesson in what it means to write. At once comic and heartbreaking, with prose that delights at every turn, this is a novel of such piercing love and tenderness that we are reminded that art is what remains when all else falls away"--Dust jacket flap.